Sustainability indicators in municipal waste management in the municipality of Salvaterra (Ilha do Marajó-Pará) - Ogorodnik, Maria Eduarda Assumption; Borges, Heloiza Santos; de Castro, Anne Sanches; do Nascimento, Deyved Leonam Guimarães; Dourado Junior, Octavio Cascaes; Chaves, Andrea Fagundes Ferreira (Seven Editora, 2023)
The municipality of Salvaterra is located on Marajó Island and is one of the Brazilian municipalities where the final disposal of solid waste still occurs incorrectly. In this sense, the present work aimed to analyze the current scenario of solid waste management in the municipality of Salvaterra/PA through the system of sustainability indicators PEIR (Pressure-State-Impact-Response). The results show thatthe waste generated in the municipality is disposed of in   a dump located near the city and that the health service waste, produced  in hospitals, is burned in the open air in this same dump. There is no type    of solid waste management, waterproofing of soil or treatment of gases generated by the decomposition of the city's waste, which further aggravates the situation because the water resources and soil can be contaminated by slurry, the population is  vulnerable to  the contagion of vector-borne diseases and the burning of health service waste  contributes to air pollution and can also cause respiratory diseases.  Thus, it is noted that the system of sustainability indicators PEIR proved to be an effective tool to perform the first data collection and municipal diagnosis on the reality of waste in Salvaterra, thus being a starting point that can support actions, stimulate and direct new studies and complement the construction of the municipal waste management plan. DOI: https://doi.org/10.56238/methofocusinterv1-087